Implementasi Literasi Digital melalui Film Dokumenter dalam Pelaksanaan Pembelajaran IPS (Kelas VII di SMP Negeri 2 Grogol Kabupaten Sukoharjo) - Karima, Evia Rizqi; Ginanjar, Asep (Sosiolium: Jurnal Pembelajaran IPS, 2021)
The learning stage of the school literacy movement integrates literacy with the teaching and learning process in all subjects. State junior High School of 2 Grogol has implemented the school literacy movement for three years and has strengthened digital literacy in learning. The research method used is a qualitative method. The results of the research on digital literacy social studies learning planning and implementation through documentary films at State Junior High School of 2 Grogol are good. Evaluation of the process of implementing social studies learning through documentary films, students are very enthusiastic and actively participate in learning in zoom. Obstacles in implementing digital literacy social studies learning through documentary films, include teacher laptop speakers that cannot be connected to the zoom, students' internet signals that disappear and arise.